MODELLING AND ANALYSIS OF I .C ENGINE CONNECTING ROD - S., Suresh kumar; R., Prasanna vignesh; C., Krishnamurthy; R., Samuel sundar; S., Murali (International Journal of Psychosocial Rehabilitation, 2020)
The key aim of this project is to investigate the varying stress involved for a forged steel connecting rod. This study deals with two things, namely design and stress analysis of the connecting rod. The design of connecting rod will be discussed in the first part of the study, like Measuring dimensions of forged steel connecting rods and drawing the 2D profiles and converting it to 3D parts, after which assembling the parts of the connecting rod and also Part file is converted to IGES file by using Solid Edge V20 software. Secondly, the connecting rod tension analysis contains the following steps: importing the IGES file to Ansys Workbench Simulation Environment, meshing the connecting rod at different element size in different surface areas, applying the constraints and loads in suitable surface area of the connecting rod and Solving for the variable stresses involved in forged steel material-based connecting rods.